2002
DOI: 10.1073/pnas.012588099
|View full text |Cite
|
Sign up to set email alerts
|

Functional requirement of aquaporin-5 in plasma membranes of sweat glands

Abstract: The distribution and function of aquaporins (AQPs) have not previously been defined in sweat glands. In this study, AQP1, AQP3, and AQP5 mRNA were demonstrated in rat paw by reverse transcription (RT)-PCR, but AQP2 and AQP4 were not. AQP1, AQP3, and AQP5 protein were confirmed in these tissues by immunoblotting. AQP1 was identified in capillary endothelial cells by immunohistochemical labeling, but not in sweat glands or epidermis. Abundant AQP3 expression was seen in basal levels of epidermis, but not in swea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
175
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(194 citation statements)
references
References 43 publications
(39 reference statements)
16
175
1
2
Order By: Relevance
“…AQP1 has two consensus sequences for N-linked glycosylation at amino acids 42 and 205 (Huebert et al, 2002;Moon et al, 1995). Glycosylation has been confirmed by the deglycosylation studies conducted by Preston et al (1992) and Nejsum et al (2002); moreover, the antibody supplier's data sheet on "specificity of the antibody" has cited the binding of the antibody to glycosylated AQP1. The quantity of AQP1 protein increased steadily from P0.5 to P30.0.…”
Section: Developmental Expression Of Aqp1 Proteinmentioning
confidence: 86%
“…AQP1 has two consensus sequences for N-linked glycosylation at amino acids 42 and 205 (Huebert et al, 2002;Moon et al, 1995). Glycosylation has been confirmed by the deglycosylation studies conducted by Preston et al (1992) and Nejsum et al (2002); moreover, the antibody supplier's data sheet on "specificity of the antibody" has cited the binding of the antibody to glycosylated AQP1. The quantity of AQP1 protein increased steadily from P0.5 to P30.0.…”
Section: Developmental Expression Of Aqp1 Proteinmentioning
confidence: 86%
“…Aquaporin-5 (AQP5) is a member of a family of water channel proteins [22,23] and is expressed at high levels in the lung, salivary gland and lacrimal tissues [1][2][3][4][5][6][7][8]. In the human, mouse and rat genome, the Aqp5 gene is located in a closely spaced tandem arrangement with Aqp2 and Aqp6 [24].…”
Section: Discussionmentioning
confidence: 99%
“…The Aqp5 gene encodes the water channel protein aquaporin-5 (AQP5) and is highly expressed in lung, salivary glands and lacrimal tissue [1][2][3][4][5][6][7][8]. In adult rat lung alveolar epithelium, AQP5 is selectively expressed on the apical surface of alveolar epithelial type I cells [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the expression of AQP5 in the skin was believed to be restricted to the sweat gland cells in the dermis, although its role in sweat secretion is not clear (Nejsum et al, 2002;Song et al, 2002;Inoue et al, 2013). However, we have recently reported the first inherited skin disease associated with aquaporin mutations and have shown that AQP5 is expressed throughout the epidermis, albeit at a much lower level than seen in the sweat glands, with a particularly strong localisation at the plasma membrane in keratinocytes of the stratum granulosum of the palmar epidermis (Fig.…”
Section: Aqp5mentioning
confidence: 99%